Butterfly abundance and presence of their host plant at Bantimurung-Bulusaraung National Park, Indonesia. Issue 1 (April 2020) - Aminah, S N; Nasruddin, A; Abdullah, T; Fatahuddin,
Abstract: The famous butterfly conservation areas in South Sulawesi, Bantimurung-Bulusaraung National Park, are gradually being replaced by intensively used farmland especially in lowland and submontane regions. The objectives of the research were to identify butterfly species and their host plant served as larvae food, nectar and pollen source in three different altitudes at Bantimurung-Bulusaraung National Park. The research was conducted based on transect methods at Bantimurung-Bulusaraung National Park, Maros Regency, South Sulawesi, Indonesia from April to October 2018. Butterflies and their food were observed in three locations at different altitudes of 0-300 m above sea level (asl), 400-700 m asl, and above 700 m asl. The observation indicates a variation in the butterfly species found in different altitudes based on the presence of host plants. A total of 59 individual butterfly samples collected were divided into four families: Papilionidae (7 species), Pieridae (2 species), Nymphalidae (1 species) and Saturniidae (1 species). A further dispersal study based on seasons is needed in order to build a good taxonomic database for Sulawesi butterflies conservation.